A prime a day keeps calories away: The effects of supraliminal priming on food consumption and the moderating role of gender and eating restraint. (1st October 2016) - Minas, Randall K.; Poor, Morgan; Dennis, Alan R.; Bartelt, Valerie L.
Abstract: The link between intentions and action in weight control is weaker than previously thought, so recent research has called for further investigation of ways to improve weight control that bypass conscious intentions. Priming has been shown to have effects on individual behavior in a variety of contexts by influencing subconscious cognition. This paper investigates the effects of semantic priming using healthy body image, goal-oriented words on food consumption. The moderating role of both restrained eating and gender is investigated. 161 participants were involved in an experiment using a novel version of a scrambled sentence priming game. The outcome measure was the number of kilocalories consumed, examined using a between subjects ANCOVA with priming, gender, restrained eating index, self-reported BMI, and two interaction terms (priming x gender, and priming x restrained eating index). There was no main effect of priming but there was an interaction of priming with gender. Females consumed significantly fewer kilocalories after being exposed to priming words related to a healthy body image (i.e. "slim", "fit, ") compared to females receiving the neutral prime, with a medium effect size (d = 0.58). The body image prime did not significantly affect food intake for males, nor did it have a differential effect on restrained eaters. This study shows that priming can be an effective method for influencing females to reduce food intake, regardless of whether they are restrained or unrestrained eaters. Future studies could investigate whether different priming words related to a male's healthy body image goal (i.e. "buff, " "muscles, " etc.) would similarly reduce food intake for males.